2007
DOI: 10.1111/j.1600-0625.2007.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

A graft model for hair development

Abstract: Follicular cell implantation (FCI) is an experimental cell therapy for the treatment of hair loss that uses cultured hair follicle cells to induce new hair formation. This treatment is based on the demonstration that adult dermal papilla cells (DPC) retain the hair inductive capacity they acquired during hair morphogenesis in the embryo. For FCI, hair inductive cells are isolated from scalp biopsies and then propagated in culture in order to provide enough cells to generate many new follicles from a few donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Various trichogenic assays, using epithelial and mesenchymal cells, have indicated the therapeutic potential of folliculogenesis [1][2][3][4][5][6][7][8]. However, no successful clinical trials have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Various trichogenic assays, using epithelial and mesenchymal cells, have indicated the therapeutic potential of folliculogenesis [1][2][3][4][5][6][7][8]. However, no successful clinical trials have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These have the potential for large effect. For example, grafts of small numbers of cells into ectopic positions can induce hair or limbs [46,47].…”
Section: Mechanismmentioning
confidence: 99%
“…This limitation poses challenges in human hair regeneration. Although some successes have been reported (7,8), they relied on very high densities of newborn murine cells, which are impractical for preparation of engineered skin substitutes (ESS).…”
Section: Introductionmentioning
confidence: 99%